2021
DOI: 10.3390/nu13093080
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Plasma Metabolomics Profile in Pregnancy—A Study in an Ethnically Diverse U.S. Pregnancy Cohort

Abstract: Amino acids, fatty acids, and acylcarnitine metabolites play a pivotal role in maternal and fetal health, but profiles of these metabolites over pregnancy are not completely established. We described longitudinal trajectories of targeted amino acids, fatty acids, and acylcarnitines in pregnancy. We quantified 102 metabolites and combinations (37 fatty acids, 37 amino acids, and 28 acylcarnitines) in plasma samples from pregnant women in the Eunice Kennedy Shriver National Institute of Child Health and Human De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
(61 reference statements)
2
8
0
Order By: Relevance
“…In line with previous studies [15,18,28], we observed varying results for some, but not all acylcarnitines between obese women and non-obese women and between GDM cases and non-GDM women. However, our sensitivity analyses showed that the associations of C12, C10, and C10:1 with neonatal anthropometric measures remained significant even after adjustment for GDM and pre-pregnancy BMI.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous studies [15,18,28], we observed varying results for some, but not all acylcarnitines between obese women and non-obese women and between GDM cases and non-GDM women. However, our sensitivity analyses showed that the associations of C12, C10, and C10:1 with neonatal anthropometric measures remained significant even after adjustment for GDM and pre-pregnancy BMI.…”
Section: Discussionsupporting
confidence: 92%
“…Third, concomitant changes in metabolites other than acylcarnitines, such as branched-chain and aromatic amino acids, non-esterified fatty acids, and phosphatidylcholines, might induce collinearity and further complicate the associations of acylcarnitines, which is difficult to disentangle, especially when they might be highly correlated or in the same biological pathways. We previously reported that most of the maternal acylcarnitines (except C8 and C14) appeared to significantly decline in early/mid-pregnancy and rise slightly after GW30, while the sum of BCAA significantly decreased as gestation progressed, driven by changes in leucine and valine [28]. Finally, the results do not prove a causal effect of acylcarnitines on fetal growth and development.…”
Section: Discussionmentioning
confidence: 56%
“…Metabolites were measured in maternal urine samples collected at three time points during pregnancy (median GA in weeks (25 th , 75 th percentile): T1, 10 ( 8 , 13 ); T2, 21 ( 19 , 22 ); T3, 29 ( 27 , 31 )), Figure 2 . We used the AbsoluteIDQ® p180 Urine Extension kit (Biocrates Life Sciences AG, Innsbruck, Austria) to perform the targeted mass spectrometry (MS)-based quantitative metabolomic assay that directly measured metabolite concentrations in urine samples.…”
Section: Methodsmentioning
confidence: 99%
“…The ability of the blood metabolome to reflect internal and external perturbations [15,16] of the organism makes it one of the most important information layers for comprising a global picture of the condition of the individual at a specific point in time [17]. The versatility of the blood metabolome has provided fruitful ground for an impressive body of work investigating rapid [18,19] and slow [20,21] changes in the body. Modern metabolomic approaches allow the identification of characteristic patterns of low molecular weight compounds and associate them with the development of pathologies [22][23][24], lifestyle [25,26], and eating habits [27][28][29] in both personalized mode [10,30,31] and large cohorts [32,33].…”
Section: Serum and Plasma Metabolome As A "Snapshot" Of A Human Biochemistrymentioning
confidence: 99%